Characterisation of protein antigen from Fasciola gigantica of different age - Estuningsih, S Endah; Widjajanti, S (Indonesian Journal of Animal and Veterinary Sciences, 1999)
The protein antigens extracted from adult fluke Fasciola gigantica, 3, 6 and 9 weeks old and newly excysted juvenile (NEJ) were identified using SDS-PAGE and immunoblotting techniques. Sera from fat-tailed sheep which artificially infected with the metacercariae of F. gigantica were used for immunoblotting. The results showed that the protein antigen profile of adult fluke, 6 and 9 weeks old flukes had similar. Bands with molecular weight between 24 kDa to 114 kDa. Protein bands with molecular weight <24 kDa and >198 kDa were also detected from the adult fluke. The use of immunoblotting technique, there were two antigenic protein molecules identified from adult fluke, NEJ and 3, 6, and 9 weeks old fluke with the molecular weight 46 kDa and 47 kDa. The protein band with molecular weight >198 kDa shown thicker on the NEJ than that of adult fluke, and 6 and 9 weeks old flukes. The role of protein with molecular weight of 46 and 47 kDa were the interested findings need to be evaluatedfor serological analysis. Â  Key words : Protein antigen, Fasciola gigantica, SDS-PAGE, immunoblotting